Republic of Slovenia : 2006 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Slovenia. (IMF Staff Country Reports; Country Report, 2006)
Slovenia is set to become the first among the new European Union member states to adopt the euro. Executive Directors emphasized the need to implement policies that increase productivity, create an efficient business environment and a flexible labor market, and improve sustainability of public finances in the face of population aging. Labor participation is also relatively low among the older and younger working-age population. To deal with these challenges, the authorities should speed up efforts to raise labor utilization by lowering marginal tax rates, improving the target of social benefits and reducing incentives for early retirement.